Combustion Synthesis of AlN (Al3O3N), BN, ZrN, and TiN in Air and Ceramic Application - Gromov A. A. Aleksandr Aleksandrovich; Maggi F. Filippo; Malikova E. V. Ekaterina; Pautova Yu. I. Yuliya Igorevna; Ilyin A. P. Aleksandr Petrovich; Popenko E. M.; Sergienko A. V.; Korotkikh A. G. Aleksandr Gennadievich; Teipel U. (2014, 2014)
Title screen